Scholarly impact of core econometrics journals: A catalog and citations-based ranking - Franklin G. Mixon; Kamal Prasad Upadhyaya (International Econometric Review (IER), 2021)
With 23 core econometrics journals now in operation, this study fills a gap in the literature by cataloguing the editorial specifications of each journal, and, more importantly, assessing their impact based on citations to research published in each over the 15-year period beginning in 2001 and ending in 2015. Our investigation reveals that about one-half of all core econometrics journals publish in an online format only, while the others publish both online and in-print. About one-fourth of all core econometrics journals are affiliated with an academic organization or society, while the same number are published by either Elsevier, Springer or Wiley. In terms of our assessment, Econometrica, Journal of Econometrics and Journal of Applied Econometrics sit atop our citations index ranking, while the relatively-new Journal of Financial Econometrics breaks into the top five, and other younger journals, such as the Journal of Econometric Methods and Econometrics, also make a strong showing in what is the first academic study assessing their productivity.
Keywords: A14; C10; C20; C30; C40; C50; 330; econometrics scholarship; journal rankings; research impact